TACC3 expression as a prognostic factor in aggressive types of adult T‐cell leukemia/lymphoma patients. (3rd August 2020) - Moritsubo, Mayuko; Miyoshi, Hiroaki; Matsuda, Kotaro; Yoshida, Noriaki; Nakashima, Kazutaka; Yanagida, Eriko; Yamada, Kyohei; Takeuchi, Mai; Suzuki, Takaharu; Muta, Hiroko; Umeno, Takeshi; Furuta, Takuya; et al.
Abstract: Introduction: Adult T‐cell leukemia/lymphoma (ATLL) is a malignant peripheral T‐cell neoplasm associated with human T‐cell leukemia virus type‐1 (HTLV‐1). The acute and lymphoma subtypes are regarded as aggressive ATLLs, and the overall survival (OS) of patients remains poor. Transforming acidic coiled‐coil‐containing protein 3 (TACC3) regulates microtubules, which are associated with cancer‐related proteins overexpressed in various cancers. Such a relationship has not been reported in hematopoietic tumors, including ATLL. Methods: We examined tissue microarrays of histological samples from 92 cases of aggressive ATLL and assessed clinical features, including TACC3 protein expression levels. Results: Compared with TACC3‐low, TACC3‐high ATLL patients were significantly older ( P  < .001), with a tendency toward pleomorphic variant over other morphological classifications ( P  = .019). TACC3‐high patients (median survival time [MST] 10.6 months, confidence interval [CI] [6.27‐15.6]) had poorer OS compared to TACC3‐low patients (MST 20 months, CI [9.43‐38.5]) ( P  = .0168). Moreover, multivariate analysis on TACC3 expression levels suggests that TACC3‐high is an independent significant prognostic factor (HR, 1.700; 95% CI, 1.037‐2.753; P  = .0355). Conclusion: Certain drugs that inhibit TACC3‐overexpressing neoplastic cells are used clinically. Further studies might highlight a key role for TACC3 in the oncogenesis and progression of ATLL.